SYSTEMATIC LITERATURE REVIEW: PENGEMBANGAN LKPD INTERAKTIF BERBASIS PBL TERINTEGRASI ARTIFICIAL INTELLIGENCE PADA MATERI SPLTV - Bukori, Ahmad; Nindiasari, Hepsi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the development, trends, and contributions of research in mathematics education through a Systematic Literature Review (SLR) approach. The method used in this study is the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), which was conducted systematically, structurally, and transparently. The subjects of this study were scientific articles published in nationally accredited journals indexed by SINTA 1 to SINTA 4 as well as internationally reputable Scopus indexed journals relevant to mathematics education, particularly those discussing the Problem Based Learning (PBL) model and students’ mathematical problem-solving abilities. Data were collected through searches on Google Scholar, SINTA, and Scopus databases using keywords such as “Problem Based Learning,” “mathematical problem-solving ability,” and “PBL in mathematics education.” The PRISMA stages included identification, screening, eligibility, and included processes to obtain articles that met the inclusion and exclusion criteria. The analyzed articles were published between 2019 to 2025 and were relevant to the focus of the study. Data analysis was carried out descriptively and qualitatively by classifying articles based on research themes, methods used, and their contributions to mathematics learning. The findings revealed an increasing number of mathematics education publications in SINTA and Scopus indexed journals, focusing mainly on innovative learning models, technology integration in learning, and the improvement of students’ critical thinking and mathematical problem solving skills. Most studies employed quantitative and mixed method approaches. These findings provide a comprehensive overview of the direction of mathematics education research development in Indonesia and may serve as a reference for researchers and educators in developing more innovative, effective, and relevant studies to meet the demands of 21st century learning.